The genetic framework for development of nephrolithiasis - Vinaya Vasudevan; Patrick Samson; Arthur D. Smith; Zeph Okeke (Asian Journal of Urology)
Over 1%–15% of the population worldwide is affected by nephrolithiasis, which remains the most common and costly disease that urologists manage today. Identification of at-risk individuals remains a theoretical and technological challenge. The search for monogenic causes of stone disease has been largely unfruitful and a technological challenge; however, several candidate genes have been implicated in the development of nephrolithiasis. In this review, we will review current data on the genetic inheritance of stone disease, as well as investigate the evolving role of genetic analysis and counseling in the management of nephrolithiasis.